2011 Triennial Surveillance Review : Overview Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This paper assesses progress in strengthening Fund surveillance and identifies needed improvements. It differs from past reviews insofar as it: (A) encompasses not only bilateral but also multilateral surveillance; and (B) steps-up external inputs in the form of studies by outside observers, commentaries, and assessment of recommendations by an external advisory group.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet